Tailoring Order Management System with Data Retention and Role-Based Access Control - BINTI KU AZMAN, KU NUR HANIS; Rahim, Nordiana (Applied Information Technology And Computer Science, 2025)
The Tailoring Order Management System with Data Retention and Role-Based Access Control (RBAC) was developed to help small tailoring businesses address issues with manual order management. This project aimed to digitize processes, improve data organization, and secure customer information for Nadimah Tailor that based in Kuala Lipis, Pahang. The Agile development methodology was used to create a web-based system with features like secure login, customer and staff management, order tracking, and automated data retention policies. System testing showed that the modules performed well, ensuring secure access, efficient order tracking, and automatic data removal after the retention period. These features enhanced productivity and minimized risks of data mismanagement. The system successfully streamlined operations and provided a user-friendly interface for staff and customers. Future work could explore integrating advanced analytics and expanding functionalities to further optimize tailoring operations.